Pengaruh Pemberian Edukasi Terhadap Kepatuhan Minum Obat Pasien Prolanis di Puskesmas Gamping 1 - Larasati, Niken; Husna, Nadia (Jurnal Indonesia Sehat, 2023)
Background: Based on the Basic Health Research (Riskesdas) in 2018, it was stated that people suffering from chronic diseases had increased compared to the 2013 Riskesdas data, including hypertension. Patients with hypertension need to be vigilant because this disease often does not cause symptoms and can cause death. This is a challenge for the government to be able to cope with the increasing population of hypertension patients in the community. Adherence and good understanding in carrying out therapy can affect blood pressure and gradually prevent complications. The Chronic Disease Management Program (PROLANIS) is a government program that involves participants, health facilities, and BPJS Kesehatan in an integrated manner as an effort to achieve therapeutic targets and optimal quality of life in an effective and efficient manner. Purpose: This study was conducted to determine the effect of education on medication adherence to PROLANIS patients at Puskesmas Gamping 1 Yogyakarta. Methods: This research is non experimental research and is analytic observational in nature. Data were collected retrospectively in June-September 2018, then the data were analyzed using the chi-square method. Result: Based on the data obtained, the distribution of adherence to the use of antihypertensive drugs was high adherence of 21.35%, moderate adherence was 48.31%, and low adherence was 28.10%. Conclusion: This study also shows that there is a significant relationship between the provision of education and compliance with PROLANIS patients taking medication at Puskesmas Gamping 1 Yogyakarta.